A proposed methodology for establishing software process development improvement for small software development firms - al-Tarawneh, Mejhem Yousef; Abdullah, Mohd Syazwan; Mat Ali, Abdul Bashah (Elsevier Ltd., 2011)
Small software development firms represent the majority of all software firms in most countries. These firms are facing the same software engineering challenges that affect large software firms.Software Process Improvement (SPI) traditional models were developed to help large and very large firms, however small software firms could not afford these models. Furthermore, they need to manage and improve their software development processes for several reasons such as dealing with the rapid technology advances, maintaining their products, satisfying the customers’ needs and sustaining their operations. This paper presents the methodology’s stages of developing a suitable software development process improvement framework by using Capability Maturity Model Integration (CMMI-DEV V1.2) as the basic model for improvement and Extreme Programming (XP) method as the basic software development method.